2020
DOI: 10.1096/fj.202001258rr
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor α in skeletal muscle is essential for T3‐mediated increase in energy expenditure

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…More importantly, the authors showed that T3 treated mice had elevated heat loss over the tail, suggesting that the animals actually needed to dissipate heat to maintain the body temperature, indicative of excess heat production in the periphery, presumably the muscle ( 22 ). Interestingly, however, it was also shown that blocking TRα1 signaling exclusively in the muscle also does not interfere with the elevation of body temperature upon thyroid hormone treatment ( 63 ).…”
Section: Central Effects Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the authors showed that T3 treated mice had elevated heat loss over the tail, suggesting that the animals actually needed to dissipate heat to maintain the body temperature, indicative of excess heat production in the periphery, presumably the muscle ( 22 ). Interestingly, however, it was also shown that blocking TRα1 signaling exclusively in the muscle also does not interfere with the elevation of body temperature upon thyroid hormone treatment ( 63 ).…”
Section: Central Effects Of Thmentioning
confidence: 99%
“…In the light of the recent studies, it seems plausible that TH primarily elevates body temperature by increasing the central set point as in pyrexia ( 22 , 62 ), which is at least partially fueled by peripheral TH action in muscle ( 22 , 39 ). However, the higher body temperature is observed in conditions with inactive BAT or browned WAT including Ucp1 knockout mice ( 22 , 62 ), as well as in mice with blocked skeletal muscle TRα1 signaling ( 63 ), which suggests that neither BAT nor muscle are absolutely required for the effect but likely can compensate for each other. Interestingly, alternative and UCP1-independent mechanisms of BAT thermogenesis could play a role in this context ( 69 , 70 ); however, these pathways were not upregulated in hyperthyroid mice ( 22 ).…”
Section: Open Questionsmentioning
confidence: 99%
“…We further examined the link between Six1 function and TH signaling in skeletal muscle by performing gene set enrichment analysis (GSEA) on the Six1-cKO gene expression profiling data of Sakakibara et al We generated two gene sets from the study of Nicolaisen et al (84), where the impact of T3 treatment and muscle-specific knockout of the thyroid hormone receptor alpha gene (Thra-cKO) was examined by RNA-seq. Specifically, we generated a first gene set representing genes whose expression is significantly lower in T3-treated muscle of Thra-cKO compared to wild-types, and a second one with the genes showing the opposite behavior, with expression higher in the Thra-cKO tissue.…”
Section: Thyroid Pathway Regulation Is Impacted Negatively In Six1 Loss-of-function Conditionsmentioning
confidence: 99%
“…The R script (including package versions and session information) used to analyze data and generate the figures is provided as supplementary files Code_S1. Gene set enrichment analysis was performed using the Sakakibara data and two gene sets from the Nicolaisen et al study (84). Briefly, RNA-seq data (read counts over genes) were downloaded from NCBI GEO accession GSE146336 and analyzed in R/Bioconductor using the edgeR package (100).…”
Section: Gene Expression Profiling Data Analysismentioning
confidence: 99%
“…In skeletal muscles, TH activity regulates the processes of myogenesis and muscle regeneration [ 38 , 39 ], contractile structure [ 40 ], energy expenditure [ 41 ], mitochondrial thermogenesis, fatty acid oxidation [ 42 ], glucose uptake [ 40 ], insulin responsiveness [ 43 ], and autophagy [ 44 ]. In the context of muscle fiber type specification, hyperthyroidism promotes fast-twitch muscle phenotypes, while hypothyroidism is associated with a switch toward slow-twitch phenotype [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%